Individualised physical activity and physiotherapy behaviour change intervention tool for breast cancer survivors using self-efficacy and COM-B: feasibility study. (4th March 2022) - Johnson, Marie-Clare; Judah, Gaby; Cunningham, Deborah; Olander, Ellinor K.
Abstract: Objective: Breast cancer survivors who are physically active have lower recurrence and all-cause mortality. Breast cancer survivors often struggle to initiate and maintain physically active lifestyles. Barriers include psychosocial, environmental, and musculoskeletal factors. An individualised physical activity intervention, informed by physiotherapy and behaviour change principles, may comprehensively address these barriers. This study tests the feasibility of this intervention. Methods: Following ethical approval and informed consent, stage-I and stage-II breast cancer survivors within 18 months of diagnosis were recruited from a secondary care NHS breast cancer unit. The intervention used tools combining musculoskeletal dysfunction, self-efficacy measurement and the COM-B model to allow personal tailoring of intervention techniques. The feasibility of recruitment, retention, acceptability and practicality of delivery of the physical activity intervention was tested using a single arm study. Results: Nine of 36 (25%) potential participants were recruited. Seven (77%) were retained to the study end. All participants reported that the intervention was acceptable. Eight would recommend the intervention and reported that their physical activity level increased due to the intervention. The intervention was practical to deliver within routine physiotherapy appointments. Conclusions: This small feasibility study has promising findings and will now need to be tested with more participants.